Trade-off-theory vs. pecking order theory and the determinants of corporate leverage: Evidence from a panel data analysis upon French SMEs (2002-2010) - Philippe Adair; Mohamed Adaskou (Cogent Economics & Finance, 2015)
We test the assumptions of trade-off theory (TOT) and pecking order theory (POT) regarding corporate leverage. The dependent variable being the debt ratio, we apply a linear model upon a balanced panel data-set of 2,370 French SMEs over the period 2002 - 2010. In accordance to TOT, trade credit acts as a signal to creditors who have no private information about the firm and access to credit relies on guarantees. The relationship between corporate leverage and the profitability of SMEs as well as growth opportunities support POT. However, the relationship between corporate leverage and the age of SMEs, as well as their size, remains inconclusive with respect to both theories.
Keywords: C23; G32; 330; capital structure; corporate leverage; panel data; pecking order theory; trade-off theory